Changes in radiographic findings and plantar pressure distribution following forefoot reconstructive surgery for patients with rheumatoid arthritis. Issue 6 (1st November 2020) - Lee, Hyunho; Ishikawa, Hajime; Shibuya, Tatsuaki; Takai, Chinatsu; Nomura, Yumi; Kobayashi, Daisuke; Abe, Asami; Otani, Hiroshi; Ito, Satoshi; Nakazono, Kiyoshi; Ryu, Keinosuke; Ishii, Takao; et al.
Abstract: Objectives: To evaluate changes in radiographic findings and plantar pressure distribution after rheumatoid forefoot surgery. Methods: This study was performed on patients with rheumatoid arthritis (RA) who underwent Swanson implant arthroplasty for the 1st metatarsophalangeal (MTP) joint combined with shortening oblique osteotomy at the 2nd through 5th metatarsal necks (group Sw, 55 feet). The following two groups were used as controls: group NS, consisting of 75 feet in RA patients without scheduled forefoot surgery, and group HC, consisting of 24 feet in healthy female subjects. Plantar pressure distribution, and radiographic findings of hallux valgus angle, the angle between the metatarsal bones, talocalcaneal angle, calcaneal pitch angle and calcaneo-first metatarsal angle (CFMA) were measured pre- and one year postoperatively. Peak pressure was measured in nine sections. Results: Calcaneal pitch angle decreased and CFMA increased in group Sw. Peak pressure at the 1st interphalangeal joint (IP) and the 2nd and 3rd MTPs in group Sw decreased, while that at midfoot increased. Conclusion: While the clinical outcome in group Sw was favorable, postoperative longitudinal arch decreased. Postoperative peak pressure at the 2nd through 5th MTPs was comparable with that in group NS; however, it was significantly lower than that in group HC.